COHERENCE OF THE CLIMATE POLICIES OF THE EUROPEAN UNION AND UKRAINE - Skuibida, Olena; Garkusha, Maryna (Sworld-Us Conference proceedings, 2022)
Environmental policy and regulation are key to promoting a green transformation of the economy that is essential for Ukraine in the framework of significant technogenic load as the urgency of post-war reconstruction. When developing measures to overcome /